Dirosah Muqoronah Nahwiyah: Al-Khilafu Baina Al-Kholil bin Ahmad wa Sibawaeh Fi Ba'di Masail Nahwiyah - Ismail, Ismail (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2017)
Kholil bin Ahmad was born as the Arabs of the tribe al-Azad al-Yamaniyah in the year 100 AH and died in 174. He was nicknamed Mr. Arab Nahwu decent, because he was the first to lay the foundations of qiyas, ta'lil and awamil and develop. Kholil bin Ahmad not compiled a book specifically discusses nahwu, because he did not deign authored a book on disciplines teah compiled others where teachers 'Isa ibn Umar "has compiled a book al-Jami' and al-Ikmal that explores the science syntax (nahwu) , But his thinking has been stated in the book of the work of al-Imam Sibawayh one of his students. Imam Sibawayh known by the nickname 'Ajam indicating that he came from Persia. His full name Amr bin Uthman Qunbar, Kahir in the area Baidha 'a village in Persia in the year 148 H. He included scholars who contributed in the development and enhancement of science nahwu Basrah. He was one of the disciples bin Ahmad al-Kholil recognized wit and cleverness in Nahwu problem of amyl and awamil later by him coalesced into al-Kitab where ideas contained therein banya al-Khalil. The fact that there is in the Book also there has been a disagreement between al-Khalil and Sibawayh on some issues Nahwu science. The difference between al-Khalil and Sibawayh very interesting to study because they both come from one stream madhab nahwu namely Bashrah. Both also very close relationship between teachers and students. This article peeling difference between the two, then the author describes the data found by the deductive method and indutif.